(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE "HUMAN RESOURCES AND MODERN PROFESSIONS IN THE WORLD" – Aachen, Germany, 2024)
Enterprise and Organizations are ahead put purposes reach , product work release increase and them to consumers delivery in giving mutual with each other communications take they go People consumption goods to customers on time good quality and defined in varieties delivery to give in providing , industry trade with enterprises organizations between contact in fortification wholesale trade organizations separately importance occupation is enough.